2017
DOI: 10.24075/brsmu.2017-01-02
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Staphylococcus epidermidis strains in patients of the Neonatal Intensive Care Unit

Abstract: ГЕНЕТИЧЕСКИЙ ПОЛИМОРФИЗМ ГОСПИТАЛЬНЫХ ШТАММОВ STAPHYLOCOCCUS EPIDERMIDIS, ВЫДЕЛЕННЫХ У НОВОРОЖДЕННЫХ ОТДЕЛЕНИЯ РЕАНИМАЦИИ И ИНТЕНСИВНОЙ ТЕРАПИИStaphylococcus epidermidis -представитель нормальной микрофлоры человека, способный вызывать опасные за-болевания у новорожденных с очень низкой и экстремально низкой массой тела при рождении. Различные штаммы S. epidermidis обладают разным спектром генов, ассоциированных с их резистентностью к антимикробным препа-ратам и патогенностью. По результатам анализа данных пол… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This clonal lineage (with ST5 as primary founder) represents the biggest group within the MLST scheme for this species. MRSE ST2 and ST22, among others, currently enclosed within CC5 but traditionally constituting its own CC (CC2), have been shown to be predominant among hospital environments (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017). In the community, a high diversity of STs have been identified among healthy individuals (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clonal lineage (with ST5 as primary founder) represents the biggest group within the MLST scheme for this species. MRSE ST2 and ST22, among others, currently enclosed within CC5 but traditionally constituting its own CC (CC2), have been shown to be predominant among hospital environments (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017). In the community, a high diversity of STs have been identified among healthy individuals (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…MRSE ST2 and ST22, among others, currently enclosed within CC5 but traditionally constituting its own CC (CC2), have been shown to be predominant among hospital environments (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017). In the community, a high diversity of STs have been identified among healthy individuals (Miragaia et al, 2007; Rolo et al, 2012; Cherifi et al, 2013; Becker et al, 2014; Widerstrom et al, 2016; Gordeev et al, 2017). In contrast, recent studies have revealed a high diversity of lineages among MRSE from both clinical and healthy individuals, with either no increased abundance of CC5 strains among clinical isolates (Jena et al, 2017) or with CC5 predominance in both settings (Rolo et al, 2012; Du et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, в родовспомогательных учреждениях Российской Федерации до настоящего времени большинство ИСМП было обусловлено Staphylococcus aureus [6]. В отдельных акушерских стационарах в последние годы стал преобладать Staphylococcus epidermidis [15], в отделениях реанимации и интенсивной терапии отмечались вспышки, вызванные Pseudomonas aeruginosa, Acinetobacter baumannii [16,17]. Эпидемиологический мониторинг позволяет своевременно идентифицировать риск ИСМП на основе данных о колонизации различных экологических ниш в медицинской организации.…”
Section: материалы и методыunclassified